THE INFLUENCE OF EXPERIENTIAL VALUE AND EXPERIENTIAL QUALITY ON REVISIT INTENTION OF WATERFRONT CITY PANGURURAN SAMOSIR REGENCY - Inriani Siallagan; Alfifto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This article aims to determine the effect of Experiential Value on revisit intention at Waterfront City Pangururan, Samosir Regency. To determine the effect of Experiential Quality on revisit intention at Waterfront City Pangururan, Samosir Regency. To determine the effect of Experiential Value and Experiential Quality on revisit intention at Waterfront City Pangururan, Samosir Regency. The type of research used in this study is a quantitative associative approach research type. In this study, the population was all visitors totaling 242,028 tourists who had visited the Waterfront City Pangururan Tourism Object, Samosir Regency throughout 2024 and the determination of the sample using the Slovin formula. This study used non-probability and purposive sampling techniques. Data collection techniques through distributing questionnaires to obtain primary data and documentation to obtain secondary data. The statistical data analysis technique used was multiple linear regression and previously carried out classical assumption tests and validity and reliability instrument tests. As well as determination testing and hypothesis testing. The results of the study indicate that the experiential value variable partially has a positive and significant effect on revisit intention at the Waterfront City Pangururan tourist attraction in Samosir Regency. The experiential quality variable partially has a positive and significant effect on revisit intention at the Waterfront City Pangururan tourist attraction in Samosir Regency. The experiential value and experiential quality variables partially have a positive and significant effect on revisit intention at the Waterfront City Pangururan tourist attraction in Samosir Regency.